Prevalence and impact of remote and hybrid work in academic health sciences libraries. - Petersen, David; Covey, Matthew; Crum, Janet (Journal of the Medical Library Association, 2024)
Objective: This study assesses the prevalence, usage, and impact of remote/hybrid work in academic health science libraries in 2022 and 2023. Due to differences in survey distribution, we focus primarily on the results of the second survey. Methods: Researchers surveyed administrators at Association of Academic Health Sciences Libraries (AAHSL) member libraries in the United States in March 2022 and library staff at academic health sciences libraries in March 2023. Results: The first survey received 71 responses that met inclusion criteria. Ninety-five percent of respondents indicated that remote/hybrid work was allowed in their libraries. Majorities indicated that remote/hybrid work had a positive impact on morale (86%), recruitment (53%) and retention (67%). The second survey received 383 responses that met inclusion criteria. 78% of respondents indicated they were allowed to work remotely, and majorities indicated remote/hybrid work positively impacted work/life balance (75%), morale/job satisfaction (69%), likelihood of staying at their current institution (64%), and productivity/overall effectiveness (58%). Respondents were less likely to accept a fully onsite (45% unlikely) or fully remote (20% unlikely) position than a hybrid one (1% unlikely). In a list of 9 factors associated with recruitment, retention, and job satisfaction, only salary and benefits ranked higher than remote/hybrid work. Conclusions: Remote/hybrid work is common in academic health science libraries and highly valued by employees. While not without challenges, remote/hybrid work appears to be a valuable tool to support recruitment, retention, and job satisfaction of workers in academic health sciences libraries. The findings of this study can inform library decision makers about future use of remote/hybrid work.